Identification of Chemical Compounds and Antioxidant Activity of Jamblang Plants (Syzygium cumini): A Systematic Literature Review - Himyatul Hidayah; Aditiya Rizky Putra Abimanyu; Ramadhina, Aisyah Salsabila; Farres Ilhamza Arrizqi (Eureka Herba Indonesia, 2024)
Antioxidants are compounds that can protect body cells from damage caused by free radicals, which can contribute to various degenerative diseases and aging. Therefore, research on the antioxidant activity of jamblang is very important to identify its health potential. This study aims to identify the key compounds contained in jamblang and investigate its potential antioxidant activity. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding compound identification and antioxidant activity in jamblang (Syzygium cumini). This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. With quercetin level which reaches 10-20% in jamblang, this suggests that this plant can be a significant natural source of this compound. In general, the results of testing the antioxidant activity of jamblang using various methods show that jamblang has strong antioxidant activity.